2018
DOI: 10.1007/s12307-017-0199-4
|View full text |Cite
|
Sign up to set email alerts
|

Positive Correlation between Matrix Metalloproteinases and Epithelial-to-Mesenchymal Transition and its Association with Clinical Outcome in Bladder Cancer Patients

Abstract: Involvement of matrix metalloproteinases (MMPs) in the pathogenesis of urothelial carcinoma elects them to be sensitive marker for clinical and prognostic implications. MMPs regulate tumor growth and invasion by inducing epithelial-to-mesenchymal transition (EMT) which is characterized by the complex reprogramming of epithelial cells and ultimately bring about major changes in the structural organization of bladder urothelium. The present study has been undertaken to evaluate the clinical relevance of MMPs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 36 publications
1
19
0
1
Order By: Relevance
“…New evidence suggests that the airway epithelium can contribute to airway remodeling through the process of EMT [31]. The hallmark trait of EMT is the downregulation of the epithelial marker E-cadherin, the upregulation of the mesenchymal markers α-SMA and Fn, and the increased expression of EMT-activating transcription factors such as Snail and MMP-7 [22,[31][32]. By comparison, broblasts can contribute to airway remodeling via accumulating in subepithelial regions, differentiating into myo broblasts, and secreting ECM components [33].…”
Section: Discussionmentioning
confidence: 99%
“…New evidence suggests that the airway epithelium can contribute to airway remodeling through the process of EMT [31]. The hallmark trait of EMT is the downregulation of the epithelial marker E-cadherin, the upregulation of the mesenchymal markers α-SMA and Fn, and the increased expression of EMT-activating transcription factors such as Snail and MMP-7 [22,[31][32]. By comparison, broblasts can contribute to airway remodeling via accumulating in subepithelial regions, differentiating into myo broblasts, and secreting ECM components [33].…”
Section: Discussionmentioning
confidence: 99%
“…EMT involves a modification of the classic epithelial phenotype and morphology to a fibroblastoid phenotype, as it favors an increase of cell migration, invasion, and resistance to anoikis and chemotherapy [ 54 , 55 ]. In the molecular context, cells undergo changes in gene expression, function, and/or activation of proteins involved in this transition [ 56 , 57 , 58 ]. EMT is characterized by the loss of the cell–cell junctions and the reorganization of the cytoskeleton, which results in the loss of apicobasal polarity and the decrease in the expression of canonical epithelial markers such as E-cadherin, cytokeratins, ZO-1 [ 59 ].…”
Section: Epithelial–mesenchymal Transition (Emt)mentioning
confidence: 99%
“…EMT is characterized by the loss of the cell–cell junctions and the reorganization of the cytoskeleton, which results in the loss of apicobasal polarity and the decrease in the expression of canonical epithelial markers such as E-cadherin, cytokeratins, ZO-1 [ 59 ]. This is followed by a gain of mesenchymal markers such as N-cadherin, vimentin, fibronectin, α-SMA, as well as an increase in the expression and activation of the TFs that regulate EMT, such as Twist, Snail, Slug, ZEB, and β-catenin [ 57 , 60 ]. These TFs regulate the expression of genes that favors cell migration and invasive processes [ 60 , 61 ] and contribute to the disruption of cell junctions by transcriptionally repressing CDH1 , OCLN , and CLDN [ 62 , 63 , 64 ].…”
Section: Epithelial–mesenchymal Transition (Emt)mentioning
confidence: 99%
“…MMPs act important roles in tissue remodeling associated with various biology processes such as morphogenesis, angiogenesis, tissue repair, and metastasis. MMPs are also important components of cells invasion capable of degrading a range of ECMs proteins allowing cancer cells to migrate and invade [ 30–32 ]. Recent researches confirmed that lncRNAs regulate tumor invasion and metastasis partly because of their abilities to influence the expressions of MMPs.…”
Section: Lncrnas Participate In Process Of Bc Invasion and Metastasismentioning
confidence: 99%